Floating type multilevel porous structure starch aerogel as well as preparation method and application thereof
By preparing floating multi-stage pore structure starch aerogel, the existing starch aerogel has solved the problems of low photothermal conversion efficiency and poor water absorption capacity, and has achieved efficient photothermal conversion and seawater desalination effects, and the process is simple and cost-effective Low.
Patent Information
- Application Number
- CN202411502047.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
AI Technical Summary
The application of existing starch aerogels in the fields of photothermal evaporation and seawater desalination is limited by their low photothermal conversion efficiency, poor water absorption capacity, high cost and time consumption.
The preparation method of floating multi-stage pore structure starch aerogel is adopted. The starch, initiator, crosslinking agent and water is mixed to carry out a water bath heating reaction, and black light absorbing material is added for gelatinization, and then refrigerated and frozen under vacuum conditions. and lyophilized to form an aerogel with high porosity and floating characteristics.
The photothermal conversion efficiency, water absorption performance and evaporation efficiency of the aerogel are improved, production costs and time-consuming, and efficient seawater desalination effect is achieved with green and renewable.
Smart Images

Figure CN119463275A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photothermal evaporation materials, and in particular to a floating multi-level pore structure starch aerogel and a preparation method and application thereof. Background Art
[0002] As the global water shortage problem becomes increasingly serious, finding efficient and sustainable desalination technology has become an important issue that needs to be addressed. Traditional desalination technologies such as reverse osmosis and distillation have problems such as high energy consumption and high cost. Solar-driven desalination technology has attracted widespread attention due to its environmental friendliness and high efficiency and energy saving. At present, how to improve the efficiency and stability of solar desalination systems is the focus and difficulty of research. Aerogels are ideal matrix materials for solar evaporators due to their excellent water transport properties. Aerogels can also optimize their desalination performance by adjusting the external 3D structure and adjusting the internal pore structure of the aerogels.
[0003] Starch aerogel is a porous material made from starch, which has the characteristics of low density, large specific surface area, and high porosity. It has potential application value in the fields of photothermal evaporation, seawater desalination, and adsorption. However, the existing starch aerogel preparation method is costly and time-consuming. The resulting aerogel has a single pore structure, poor water absorption capacity, and the heat absorption efficiency and evaporation efficiency need to be improved. It does not have floating characteristics, resulting in poor photothermal conversion efficiency, which limits its application in the field of photothermal evaporation material technology and seawater desalination.
[0004] Therefore, it is necessary to provide a multi-level pore structure aerogel with high photothermal conversion efficiency. Summary of the invention
[0005] In view of this, the present application provides a floating multi-level pore structure starch aerogel and a preparation method and application thereof, which are used to solve the problem of how to improve the photothermal conversion efficiency of the aerogel.
[0006] In order to achieve the above technical objectives, this application adopts the following technical solutions: In a first aspect, the present application provides a method for preparing a floating multi-level pore structure starch aerogel, comprising the following steps: S1. Mix starch, an initiator, a cross-linking agent and water, and heat the mixture in a water bath to obtain a first starch paste; S2. Adding a black light-absorbing material to the first starch paste, heating and gelatinization reaction to obtain a second starch paste; S3. After pre-drying the second starch paste, refrigeration, freezing and freeze-drying are performed in sequence under vacuum conditions to obtain a floating multi-level pore structure starch aerogel.
[0007] Preferably, in step S1, the initiator includes ammonium persulfate, the cross-linking agent includes N,N′-methylenebisacrylamide; the mass ratio of the initiator to starch is 0.5-5:100, the mass ratio of the cross-linking agent to starch is 0.5-2:100, and the mass ratio of water to starch is 5-15:1.
[0008] Preferably, in step S1, the temperature of the water bath heating reaction is 65-70° C. and the time is 30-45 min.
[0009] Preferably, in step S2, the black light-absorbing material includes one or more of copper sulfide, cuprous sulfide, copper oxide, polydopamine, silver oxide, and graphene oxide.
[0010] Preferably, the mass ratio of the black light absorbing material to the starch is 10-50:100, and the particle size of the black light absorbing material is 50 nm±10 nm.
[0011] Preferably, in step S2, the temperature of the heating gelatinization reaction is 95-100°C.
[0012] Preferably, in step S3, the pre-drying temperature is 30-60°C.
[0013] Preferably, in step S3, the refrigeration temperature is 4 to 8°C, and the time is 12 to 16 hours; the freezing temperature is -25 to -30°C, and the time is 24 to 36 hours; the freeze-drying temperature is -40 to -50°C, and the time is 24 to 36 hours.
[0014] In a second aspect, the present application provides a floating multi-level pore structure starch aerogel.
[0015] In a third aspect, the present application provides an application of a floating multi-level pore structure starch aerogel in the field of seawater desalination.
[0016] The beneficial effects of this application are as follows: In the present application, starch is first cross-linked with a cross-linking agent, and then a black light-absorbing material is added for gelatinization to obtain a multi-level pore structure starch aerogel, which has high porosity, light weight, floating properties, a small static water contact angle, good water absorption performance, and good heat absorption performance, with high thermal conductivity and evaporation efficiency, high photothermal conversion efficiency, and can improve the seawater desalination effect.
[0017] The preparation method of the present application has simple process, convenient operation, high production efficiency and low energy consumption, and the prepared starch aerogel is green and renewable. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1Schematic diagram of "CYL@CuS-SA" prepared in Example 2 (1a), schematic diagram of the cross section of "CYL@CuS-SA" (1b), and schematic diagram of the floating of "CYL@CuS-SA" (1c); Figure 2 The static water contact angle test results of "CuS-SA" prepared in Example 1 and pure starch aerogel prepared in Comparative Example 1 at room temperature; Figure 3 The scanning electron microscope images of different starch aerogels; Figure 4 This is a diagram of heat absorption of different starch aerogels under xenon light illumination; Figure 5 This is the test data diagram of evaporation efficiency of different starch aerogels; Figure 6 The absorption curve of the “CuS-SA” prepared in Example 1 in the solar spectrum band; Figure 7 This is the test data of evaporation efficiency of starch aerogel with different CuS contents. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0020] The present application provides a method for preparing a floating multi-level pore structure starch aerogel, comprising the following steps: S1. Mix starch, an initiator, a cross-linking agent and water, and heat the mixture in a water bath to obtain a first starch paste; S2. Adding a black light-absorbing material to the first starch paste, heating and gelatinization reaction to obtain a second starch paste; S3. After pre-drying the second starch paste, refrigeration, freezing and freeze-drying are performed in sequence under vacuum conditions to obtain a floating multi-level pore structure starch aerogel.
[0021] In the present application, an initiator is first added to promote the cross-linking reaction between the cross-linking agent and the starch hydroxyl group to form a stable starch aerogel structure (first starch paste) with high porosity and secondary pores. After the black light-absorbing material is added, the black light-absorbing material can be evenly and abundantly distributed on the surface of the first starch paste. The black light-absorbing material can also be used to enhance the light-absorbing capacity of the material, thereby increasing the photothermal effect. After gelatinization, the water in the starch granules will evaporate, causing the starch granules to absorb water and swell, eventually forming a paste-like substance. The gelatinization process makes the starch molecular chains more fluid, forming a colloidal network. Finally, through refrigeration, freezing, and freeze-drying, the water in the colloidal network is evaporated and pores are further formed, thereby obtaining a multi-level pore structure starch aerogel with good heat absorption performance, high evaporation efficiency, and strong water absorption capacity.
[0022] In step S3, before pre-drying, the second starch paste is also poured into a 3D structure mold, and the mold includes a flat 3D mold, a cylindrical 3D mold, and a conical 3D mold. By shaping in a 3D structure mold, a multi-level pore structure starch aerogel with a recessed lower part can be obtained, and the aerogel can be placed on the foam to achieve the purpose of floating. The buoyancy can improve the efficiency of heat absorption and heat transfer, so that sunlight can directly irradiate the aerogel, and the heat can be more evenly transferred to the liquid surface, thereby improving the evaporation efficiency. The starch aerogel obtained by the preparation method of the present application will form pores inside, and then by using different 3D structure molds, cylindrical or conical channels can be formed on the upper part to further form multi-level channels. The multi-level channels can increase the effective contact area of the evaporator, thereby improving the heat exchange efficiency between water and the aerogel, which helps to heat the liquid more evenly and improve the overall evaporation effect.
[0023] It is worth noting that the flat 3D mold includes but is not limited to a mold with a rectangular inner space, the cylindrical 3D mold includes but is not limited to a mold with a plurality of cylindrical protrusions on the inner wall of the flat 3D mold, and the conical 3D mold includes but is not limited to a mold with a plurality of conical protrusions on the inner wall of the flat 3D mold.
[0024] In some embodiments, in step S1, the initiator includes ammonium persulfate, and the crosslinker includes N, N'-methylenebisacrylamide; the mass ratio of the initiator to starch is 0.5-5:100, the mass ratio of the crosslinker to starch is 0.5-2:100, and the mass ratio of water to starch is 5-15:1. Excessive use of initiator will lead to too fast reaction speed and excessive crosslinking of the chemical network of the gel, thereby affecting the pore structure and swelling performance of the gel, making the gel hard and brittle, which is not conducive to the formation of a uniform aerogel network; too little initiator may not effectively initiate the polymerization reaction, resulting in insufficient formation of the gel network, reduced gel strength, and insufficient swelling performance; and when the amount of crosslinker is insufficient, the aerogel cannot form a sufficient crosslinked network, thereby affecting its porous structure and physical and chemical properties. When the amount is too high, the inside of the aerogel becomes compact, affecting its porous structure.
[0025] In some embodiments, in step S1, the temperature of the water bath heating reaction is 65-70° C. and the time is 30-45 min.
[0026] In some embodiments, in step S2, the black light-absorbing material includes one or more of copper sulfide, cuprous sulfide, copper oxide, polydopamine, silver oxide, and graphene oxide.
[0027] In the present application, the black light-absorbing material can effectively absorb radiation from sunlight or other light sources and convert light energy into heat energy, while the porosity of starch aerogel can make the black light-absorbing material more evenly distributed, further improving the overall light absorption efficiency.
[0028] In some embodiments, the mass ratio of the black light absorbing material to the starch is 10-50:100, and the particle size of the black light absorbing material is 50 nm ± 10 nm. If the amount of the black light absorbing material is too small, the aerogel will have poor heat absorption capacity, affecting the photothermal performance and evaporation performance; if the amount is too large, it will interfere with the cross-linking process of the starch or affect the chemical stability of the aerogel, and will also block the pores and affect the water transport.
[0029] In some embodiments, in step S2, the temperature of the heating gelatinization reaction is 95-100°C.
[0030] In some embodiments, in step S3, the pre-drying temperature is 30-60°C.
[0031] In some embodiments, in step S3, the refrigeration temperature is 4~8°C and the time is 12~16 hours; the freezing temperature is -25~-30°C and the time is 24~36 hours; the freeze-drying temperature is -40~-50°C and the time is 24~36 hours.
[0032] In the present application, vacuum refrigeration, freezing, and freeze-drying operations allow the water in the starch aerogel to sublime, which is beneficial to increasing the porosity of the aerogel and reducing the density.
[0033] The present application provides a floating multi-level pore structure starch aerogel with a porosity of 80-95%.
[0034] High porosity is beneficial to the evaporation performance of floating multi-level pore structure starch aerogel. The reason is that the porosity of starch aerogel gives it good air permeability, and the efficient photothermal conversion can generate enough heat to promote the evaporation of water, while the structure of aerogel allows water vapor to be discharged quickly, thereby improving the evaporation efficiency.
[0035] The present application provides an application of a floating multi-level pore structure starch aerogel in the field of seawater desalination.
[0036] The present solution is further described below through specific embodiments.
[0037] Example 1 A method for preparing a floating multi-level pore structure starch aerogel comprises the following steps: S1. 5 g potato starch, 0.04 g ammonium persulfate, 0.05 g N, N'-methylenebisacrylamide, and 50 g water were mixed in proportion, heated in a water bath at 65 ° C, and stirred for 30 min to obtain a uniform first starch paste; S2. Add 1 g of copper sulfide powder having a particle size of 50 nm to the first starch paste, heat to 95° C. with stirring to gelatinize, and obtain a second starch paste; S3. Pour the second starch paste into a flat 3D structure mold, pre-dry the mold and the second starch paste at 45°C, refrigerate them at 4°C for 12 hours, freeze them at -30°C, and then freeze-dry them at -50°C to obtain a floating multi-level pore structure starch aerogel (CuS-SA starch aerogel).
[0038] Example 2 A method for preparing a floating multi-level pore structure starch aerogel comprises the following steps: S1. 5 g potato starch, 0.04 g ammonium persulfate, 0.05 g N, N'-methylenebisacrylamide, and 50 g water were mixed in proportion, heated in a water bath at 65 ° C, and stirred for 30 min to obtain a uniform first starch paste; S2. Add 1 g of copper sulfide powder having a particle size of 50 nm to the first starch paste, heat to 95° C. with stirring to gelatinize, and obtain a second starch paste; S3. Pour the second starch paste into a cylindrical 3D structure mold, pre-dry the mold and the second starch paste at 45°C, refrigerate them at 4°C for 12 hours, freeze them at -30°C, and then freeze-dry them at -50°C to obtain a floating multi-level pore structure starch aerogel (CYL@CuS-SA starch aerogel).
[0039] Figure 1 Schematic diagram of “CYL@CuS-SA” prepared in Example 2 (1a), schematic diagram of the cross section of “CYL@CuS-SA” (1b), and schematic diagram of the floating of “CYL@CuS-SA” (1c).
[0040] Example 3 A method for preparing a floating multi-level pore structure starch aerogel comprises the following steps: S1. 5 g potato starch, 0.04 g ammonium persulfate, 0.05 g N, N'-methylenebisacrylamide, and 50 g water were mixed in proportion, heated in a water bath at 65 ° C, and stirred for 30 min to obtain a uniform first starch paste; S2. Add 1 g of copper sulfide powder having a particle size of 50 nm to the first starch paste, heat to 95 ° C with stirring to gelatinize, and obtain a second starch paste; S3. Pour the second starch paste into a conical 3D structure mold, pre-dry the mold and the second starch paste at 45°C, refrigerate them at 4°C for 12 hours, freeze them at -30°C, and then freeze-dry them at -50°C to obtain a floating multi-level pore structure starch aerogel (Cone@CuS-SA starch aerogel).
[0041] Embodiment 4-11 A method for preparing a floating multi-level pore structure starch aerogel, the other contents are the same as those in Example 2, except that the contents of CuS are 5%, 10%, 15%, 25%, 30%, 35% and 40% respectively.
[0042] Comparative Example 1 A method for preparing starch aerogel, the other contents of which are the same as those of Example 1, except that step S2 does not include adding copper sulfide powder to obtain starch aerogel (SA).
[0043] Testing and analysis The properties of the starch aerogels obtained in the examples and comparative examples were tested, and the specific contents are as follows: Solar absorption rate test: Testing standard GB / T30127-2013.
[0044] Test of heat absorption efficiency of starch aerogel: A plurality of circular grooves with a diameter of 5 cm and a depth of 1 cm are set on the foam board on the top surface of the foam box with a size of 80 cm × 40 cm × 30 cm. The aerogel to be tested (a circular piece with a diameter of about 5 cm) is placed in the groove, and the upper surface of the aerogel to be tested is covered with a layer of polyethylene film to shield the influence of thermal convection. The lower surface of the film to be tested is connected to a K-type thermocouple to test the temperature of the surface of the film to be tested, and a four-channel temperature recorder (UT325F) is used to record the real-time temperature. The entire foam box is wrapped with tin foil to shield the surrounding radiation. The pure floating multi-stage pore structure starch aerogel (Comparative Example 1) is a blank control, and the lower surface of the polyethylene film is connected to a K-type thermocouple to test the temperature of the polyethylene film and the air surface, and a solar photometer (TES-132) is used to measure the solar power.
[0045] Evaporation efficiency test of starch aerogel: 3.5wt% salt water was added to a round glass cup with a size of 10cm×10cm×150cm to simulate seawater. The glass cup was placed on a balance connected to a computer for real-time recording. Data was recorded every 30s, and the solar power was measured using a sun photometer (TES-132).
[0046] Static water contact angle test of starch aerogel: The contact angle of the sample was measured using a contact angle meter (JC2000C2E). The water drop size used in the test was 3 μL, the fitting method was polynomial fitting, the calculation method was the tangent method, and 5 points were selected for each sample for measurement, and the average value was taken.
[0047] Surface morphology of starch aerogel was detected by scanning electron microscope (JSM-6510).
[0048] Evaporation rate test: The mass change of water in the beaker is recorded in real time by a balance and the evaporation rate is calculated by formula (1). Formula (1), Where m1 and m0 refer to the weight of water before and after illumination, s is the area of the sample being tested, and t is the time for water evaporation.
[0049] The evaporation efficiency is calculated by formula (2): Formula (2), where v is the evaporation rate, hlv is the enthalpy change, and qsolar is the solar flux.
[0050] Figure 2The static water contact angle test results of the "CuS-SA" aerogel prepared in Example 1 at room temperature are shown, and the contact angle is 0°, indicating that the aerogel prepared in Example 1 has excellent water absorption performance. The contact angle is a key parameter for measuring the wettability of the material surface. It reflects the interaction between the liquid and the solid surface. A contact angle of 0° means that the aerogel surface has an extremely high affinity for water, allowing water molecules to fully spread on the aerogel surface, thereby achieving efficient water absorption. This excellent water absorption performance is crucial to the seawater desalination process, which directly affects the efficiency of the material in absorbing and transferring water from seawater. Materials with high water absorption can more effectively extract fresh water from seawater and improve the overall performance of the desalination process. In addition, good water absorption performance allows the aerogel to absorb more water in a short period of time, which is beneficial to improving the processing capacity of the seawater desalination device and reducing energy consumption.
[0051] like Figure 3 As shown, Figure 3 a and 3b show the microscopic surface structure of the CuS-SA aerogel prepared in Example 1 at 50 times and 90 times magnification, respectively. Figure 3 c and 3d show the corresponding structure of comparative example 1. The results show that the CuS-SA aerogel prepared by the present application has porous characteristics and has efficient water absorption performance. The porous structure of CuS-SA aerogel provides aerogel with an extremely high specific surface area, so that CuS-SA aerogel can produce more contact points with water molecules, thereby enhancing its water absorption capacity. Under 50 times and 90 times magnification, the microscopic pores inside the CuS-SA aerogel can be clearly observed. These pores not only increase the surface area of the material, but also provide channels for penetration and diffusion for water molecules, which is conducive to the aerogel being able to quickly absorb water during the desalination process, thereby improving the efficiency of the entire desalination process. In addition, the porous structure of CuS-SA aerogel also helps to reduce the density of the material, making it more lightweight, which is a significant advantage for application scenarios such as desalination that require a large amount of processing materials. It also helps to improve the thermal insulation performance of the material, because the air in the pores is a material with good thermal insulation performance.
[0052] Figure 4The heat absorption of aerogels prepared in different embodiments under xenon lamp illumination is demonstrated. The results include a comparison of the heat absorption performance of the CuS-SA aerogel prepared in Example 1, the "cylindrical channel CYL@CuS-SA aerogel prepared in Example 2, the "conical channel Cone@CuS-SA aerogel prepared in Example 3, and the comparative example SA aerogel. Under xenon lamp illumination, the aerogels prepared in Examples 1-3 show more excellent heat absorption performance than the pure starch aerogel prepared in Comparative Example 1. The reason is that the addition of black light-absorbing materials enhances the aerogel's ability to absorb light, thereby improving its photothermal conversion efficiency. Due to its high light absorption rate, black materials can effectively convert absorbed light energy into heat energy, which is crucial to improving the evaporation efficiency in the seawater desalination process. In addition, the porous structure of Examples 1-3 not only increases the specific surface area of the aerogel, providing more contact area to promote the adsorption and evaporation of water molecules, but also helps to reduce heat loss during heat conduction, further improving the photothermal conversion efficiency. Through the design and material selection of this application, the performance of aerogel in seawater desalination is improved, and it has broad prospects in the application of photothermal materials. Figure 5 The evaporation rate curves of different starch aerogels are shown. Figure 5 It can be seen that compared with the SA aerogel of Comparative Example 1, the aerogel of the embodiment of the present application by adding black light-absorbing material shows a better evaporation efficiency. The reason is that the addition of black material has a higher light absorption rate, which can effectively capture the light energy in sunlight and convert it into heat energy. This process not only improves the aerogel's absorption of light energy, but also improves its photothermal conversion efficiency, thereby achieving a more efficient evaporation rate in the seawater desalination process. In addition, the porous structure of the aerogel prepared by the embodiment of the present application also provides ideal conditions for the rapid transmission and evaporation of water. The porous structure increases the surface area of the aerogel in contact with water, which promotes the rapid absorption and evaporation of water. Combined with the high photothermal conversion efficiency of the black light-absorbing material, these aerogels show excellent heat absorption and evaporation performance under sunlight irradiation, providing a strong material basis for achieving efficient seawater desalination.
[0053] Figure 6The solar absorption spectrum of the CuS-SA aerogel prepared in Example 1 is shown, indicating that the aerogel has a high solar light absorption rate, and the efficient photothermal conversion ability can directly increase the evaporation rate, thereby increasing the fresh water output and improving the desalination efficiency. CuS is a narrow bandgap semiconductor material with strong absorption performance in the visible and near-infrared regions. In this application, the combination of CuS and starch-based aerogel not only enhances the light absorption capacity of the material, but also further improves the photothermal conversion efficiency by forming a porous structure, allowing light to penetrate deep into the material, increasing the contact area of photothermal conversion, and thus improving the overall photothermal performance. It can be seen that the combination of CuS and starch-based aerogel shows great application potential in the field of seawater desalination.
[0054] Figure 7 It shows that when the CuS content reaches 20%, the evaporation efficiency of CuS-SA aerogel is the highest, indicating that the appropriate CuS content is crucial to improving the photothermal performance of aerogels. CuS is a semiconductor material with photothermal properties that can effectively convert absorbed solar energy into thermal energy, thereby improving evaporation efficiency. The addition of CuS not only enhances the aerogel's ability to absorb sunlight, but its unique photothermal conversion performance helps to improve the evaporation rate of aerogels. In addition, the combination of CuS and starch-based aerogels is beneficial to improving heat absorption and evaporation performance under sunlight. It is worth noting that an increase in the CuS content can improve the light absorption capacity of the aerogel, but too much CuS may reduce the thermal stability of the material and affect its long-term evaporation performance.
[0055] The above are only preferred specific implementations of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a floating multi-level pore structure starch aerogel, characterized in that: The following steps are involved: S1. Mix starch, an initiator, a cross-linking agent and water, and heat the mixture in a water bath to obtain a first starch paste; S2. adding a black light-absorbing material to the first starch paste, heating and gelatinization reaction to obtain a second starch paste; S3. After pre-drying the second starch paste, refrigerate, freeze and freeze-dry in sequence under vacuum conditions to obtain the floating multi-level pore structure starch aerogel.
2. The method for preparing a floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S1, the initiator includes ammonium persulfate, and the cross-linking agent includes N,N′-methylenebisacrylamide; the mass ratio of the initiator to starch is 0.5-5:100, the mass ratio of the cross-linking agent to starch is 0.5-2:100, and the mass ratio of water to starch is 5-15:
1.
3. The method for preparing the floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S1, the temperature of the water bath heating reaction is 65-70° C. and the time is 30-45 min.
4. The method for preparing a floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S2, the black light-absorbing material includes one or more of copper sulfide, cuprous sulfide, copper oxide, polydopamine, silver oxide, and graphene oxide.
5. The method for preparing the floating multi-level pore structure starch aerogel according to claim 1, characterized in that: The mass ratio of the black light absorbing material to starch is 10-50:100, and the particle size of the black light absorbing material is 50nm±10nm.
6. The method for preparing floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S2, the temperature of the heating gelatinization reaction is 95-100°C.
7. The method for preparing floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S3, the pre-drying temperature is 30-60°C.
8. The method for preparing floating multi-level pore structure starch aerogel according to claim 1, characterized in that: In step S3, the refrigeration temperature is 4~8°C and the time is 12~16h; the freezing temperature is -25~-30°C and the time is 24~36h; the freeze-drying temperature is -40~-50°C and the time is 24~36h.
9. A floating multi-level pore structure starch aerogel obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the floating multi-level pore structure starch aerogel as claimed in claim 9 in the field of seawater desalination.